Child representations of disease according to age, educational level and socioeconomic status - Ruda Santolaria, María Lourdes (2009)
The study explores child representations on the identity and origin of disease according to age, educational level and socioeconomic status. Ninety children were assessed using the Child Disease Representations Interview (CDRI) inspired in seven cards graphically representing the usual treatment of children with cancer. Results show that the same element of reality can be conceptualized in multiple ways and that smaller children tend to appeal to non-serious diseases whereas older children refer to more serious ones. Children represent the disease consistently with what child development literature has depicted. Within the lower socioeconomic level, there is a delay in the access to certain concepts, which is rectified at later stages.